Age of the basement beneath the Mesozoic Lusitanian Basin revealed by granitic xenoliths from the Papôa volcanic breccia (West Iberia) - M.F. Pereira; C. Gama; J.B. Silva; Í. Dias da Silva (Geologica Acta, 2020)
The dyke of the Papôa volcanic breccia cross-cutting the Lower Jurassic sequence of the Lusitanian Basin (West Iberia) contains granitic xenoliths. In this study, for the first time, U-Th-Pb zircon analysis of two xenoliths yielded 298±4Ma for biotite granite and of 292±2Ma for two-mica granite, indicating that the pre-Mesozoic basement of the Lusitanian Basin includes Permian intrusions. These ages are close within the margin of error of the age of the Late Carboniferous granites of the Berlengas isle that with the Late Devonian high-grade metamorphic rocks of the Farilhões isles, located northwest of the study area, which form the pre-Mesozoic basement of the Lusitanian Basin. These new geochronological findings enable it to be established that Permo-Carboniferous magmatism lasted at least 13Ma, in this region of the Appalachian-Variscan belt. Furthermore, a comparison with available data from Paleozoic tectonic units of the Appalachian-Variscan belt located both in the Iberian Massif and outside it enables the suggestion to be made that the Lusitanian Basin (Peniche) most probably rests on the South Portuguese Zone, which may also be correlated with the Rhenohercynian Zone present in southwest England, and the Meguma terrane of Nova Scotia.